Evaluation of the Road Safety Education “E-drive Academy” Interactive Program in Greek Elementary Schools: A Study of 834 Fourth Grade Students - Ntina Kourmousi; Antonios Kalamatianos; Kalliopi Kounenou; Kyriakoula Merakou (Journal of Road Safety)
Road safety constitutes a crucial public health issue and there is growing research on road safety school interventions that promote responsible road use. The current experimental study explored the effectiveness of a three-month implementation of the interactive road safety education program "E-drive Academy" with fourth-grade elementary students in Greek schools of Attica prefecture. The sample consisted of 834 students (experimental group: 629; control group: 205). The evaluation questionnaire included demographics and a road safety questionnaire for use by primary education students, specifically designed to test the effectiveness of the taught modules, namely i) walking safely, ii) using the means of transport and being a passenger in a car, iii) riding a bicycle safely, iv) being a passenger in a school bus, v) locus of control, vi) knowing the traffic lights, vii) incorporating movement into daily life, and viii) orienting oneself. The data analysis revealed that the experimental group exhibited significant (p\<0.05) improvement in all taught and investigated traffic-related knowledge, skills, and attitudes post-intervention, whereas the control group did not. The present e-health intervention confirms that properly designed universal road safety education could enhance safety skills and help prevent problem behaviours.